TURUNKAN KECEMASAN PRIMIGRAVIDA DALAM MENGHADAPI PERSALINAN MELALUI MEDIA BOOKLET - Nur Ain Desta Sulasdi; Marleni (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2025)
The labor and delivery process for primigravida mothers tends to be accompanied by increased fear and anxiety due to pain and discomfort. Mothers often worry about the safety of both themselves and their babies. If not managed properly, this condition can lead to several complications such as premature labor, prolonged labor, and fetal death. Health education is one of the efforts that healthcare professionals can implement to reduce anxiety and help mothers prepare for the labor and delivery process. This study aims to analyze the difference in anxiety levels after providing health education using a booklet between the intervention group and the control group. The research design used is a pretest-posttest nonequivalent control group with purposive sampling and a quantitative approach. The data analysis technique used was the Independent T-Test. The results showed that the t-value was greater than the t-table value (t = 5.315 > t-table 0.025 = 2.00), thus H0 was rejected. The significance level was 0.001, which is less than 0.05 (p < 0.05). This indicates a significant difference in anxiety levels between pregnant women who received health education using a booklet and those in the control group.Conclusion: Pregnant women who received health education using a booklet experienced a greater reduction in anxiety scores compared to those who did not receive such education. It is recommended that health education using booklets be provided routinely to pregnant women in order to help reduce maternal anxiety levels. Keywords: Health Education, Booklet, Labor Anxiety